Die Historische Geographie in Großbritannien. `A personal view´ - Simms, Anngret (ERDKUNDE, 1982)
Over the last two decades Historical Geography in Britain has been one of the most successful branches of our discipline. A passionate debate has been going on for some time now rejecting the so-called sterile historical geography of the logical positivist and propagating a turn to a 'marxist humanism'. A small but articulate group based in Cambridge considers 'that part of the geographer's false consciousness has been his focus upon landscape transformed by man rather than upon man as an agent of landscape change, upon artefacts rather than upon ideas, upon actions rather than attitudes, upon external forms rather than internal processes'(K. Baker,1975). It was the preoccupation with themes concerning the transition from feudalism to capitalism and the problems of the industrial revolution in England which established closer contact with the economic historians which led in turn to the acceptance of a new theoretical framework. The recent success may be explained by a number of factors: 1. a good infrastructure provided by the 'Historical Geography Research Group'.2. the full integration of historical geography into the curriculum of university students. 3. the publication of historical geographical textbooks as for instance the Dawson series 'Studies in Historical Geography' or 'Croom Helm Historical Geography Series'. 4. the courage of historical geographers in Britain to write popular books on their subject. 5. the existance of the 'Journal of Historical Geography', founded in 1975. There is no unified paradigm in British Historical Geography at present, but there is no doubt that it is a most creative period.